University Based on Knowledge Management to Create Sustainable Competitive Advantages - Wiyanto, Wiyanto (Universitas Negeri Semarang, 2020)
The purpose of this article is to provide a conceptual framework for the application of knowledge management to create sustainable competitive advantage at universities. In this 4.0 era, universities face many demands, challenges, opportunities and threats. A superior university is not only a large, high-rise building. However, universities must have advantages. In addition, the number of universities in the world is very large. Thus, each university must be able to compete and colaborate with other universities. The method used in writing this paper is to use literature studies. The author examines various scientific articles both national and international as well as relevant books. The conceptual results of this paper indicate that, resources owned by universities can be created, stored, updated, utilized and communicated. The resources owned by the university need to be well managed and used as advantages. Advantage created can be short term and long-term advantage. The conceptual framework of this paper can be used as a basis for a university to create sustainable advantages.